Application of Cognitive Interviewing in the Development of a Help-seeking Motivation Scale for Patients with Schizophrenia - MA Rui, WANG Yu, LI Yuxin, WANG Zhengjun, ZHOU Yuqiu (Zhongguo quanke yixue, 2023)
Background The accuracy of data collection can be affected by bias in the understanding of the items between the developer and the target population during scale development. Objective To adjust the items of the Schizophrenia Help-seeking Motivation Scale using the cognitive interview. Methods A purposive sampling method was used to select 30 schizophrenia patients from a psychiatric hospital in Daqing City from December 2021 to January 2022 to attend three rounds of cognitive interviews. The interview data were collected, and coded using the Question Appraisal System (QAS-99) , and after the coding results were collated, the scale entries were adjusted by integrating respondent feedback and expert panel comments. Results During the 1st round of interview, interviewees raised doubts on 11 entries, among which three were due to wording, seven were due to vague expressions, two were due to lack of inadequate knowledge, and one was due to the difficulty in recalling. And some of the entries were revised after discussion. The results of the 2nd round of interview showed that one entry was assumed to be inappropriate and was revised after discussion. The 3rd round of interview continued until the interviewees were able to understand the entries correctly, and they thought that there was no need to further revise the entries. Conclusion The cognitive interview effectively solved the problem of understanding differences between the developer and schizophrenia patients in the development of the Schizophrenia Help-seeking Motivation Scale, thus improving the accuracy and applicability of the scale.